2016
DOI: 10.1063/1.4941444
|View full text |Cite
|
Sign up to set email alerts
|

Defect reduction in overgrown semi-polar (11-22) GaN on a regularly arrayed micro-rod array template

Abstract: We demonstrate a great improvement in the crystal quality of our semi-polar (11-22) GaN overgrown on regularly arrayed micro-rod templates fabricated using a combination of industry-matched photolithography and dry-etching techniques. As a result of our micro-rod configuration specially designed, an intrinsic issue on the anisotropic growth rate which is a great challenge in conventional overgrowth technique for semi-polar GaN has been resolved. Transmission electron microscopy measurements show a different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…Furthermore, employing shorter microrods is useful for removing additional BSFs, leading to further improvement in crystal quality. The results presented provide a very promising approach to eventually achieving (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Semi-polar GaN, particularly in the (11-22) orientation, has emerged to be a promising candidate for fabricating both light emitting diodes (LEDs) and laser diodes (LDs) with a long wavelength beyond the blue spectral region, e.g., green and yellow, which is critical for solid state lighting, visible light communications and opto-genetics. The current status of the development of (11-22) GaN on sapphire can be referred to a topical review published very recently.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, employing shorter microrods is useful for removing additional BSFs, leading to further improvement in crystal quality. The results presented provide a very promising approach to eventually achieving (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Semi-polar GaN, particularly in the (11-22) orientation, has emerged to be a promising candidate for fabricating both light emitting diodes (LEDs) and laser diodes (LDs) with a long wavelength beyond the blue spectral region, e.g., green and yellow, which is critical for solid state lighting, visible light communications and opto-genetics. The current status of the development of (11-22) GaN on sapphire can be referred to a topical review published very recently.…”
mentioning
confidence: 99%
“…This can be achieved by carefully designing micro-rod templates. Based on transmission electron microscopy and photoluminescence measurements, it has been found that the micro-rod diameter plays a vital role in effectively reducing both the dislocation density and the basal staking fault (BSF) density of the overgrown (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN, but in different manners. The BSF density reduces monotonically with increasing the micro-rod diameter from 2 to 5 lm, and then starts to be saturated when the micro-rod diameter further increases.…”
mentioning
confidence: 99%
See 3 more Smart Citations